Proposed new interior design of Mobile Office Cafe at 123, Jalan Maarof, Bangsar Park, 69000, Bangsar, Kuala Lumpur for Paper + Toast / Nurul Jannah Baharudin - Baharudin, Nurul Jannah (Faculty of Architecture, Planning and Surveying, 2012)
This Paper + Toast is actually a mobile office cafe. It is created especially for those who wish to create their own way of working. Paper + Toast was those who are looking for a business address, a working space or a different working environment from the conventional office and living room. A mobile office cafe with innovative virtual office solutions,inspiring workspace and a chic dining option for entrepreneurs,professionals and executives on-the-go.The single aim is enhancing efficiency and productivity away from the conventional office. Therefore, this mobile office cafe is set up in a fun way to make sure all the customers enjoy eating and working here. The requirements for this mobile office cafe is to full fill a mobile office cafe needs throught modernity. Besides that, the design must suit the comfort, aesthetic and practical to the owners, workers and customers.Mobile office cafe is the place where different types of activities are held in one time which are eating at the cafe and also work at the coworking space. So,this new franchiese is design to overcome the problems and also to upgrade the systems. So that,any activities can go smoothly without any disturbing.Customer’s satisfaction is a very important for this type of business.Not only that,a comfort area can create a better activities, either to the workers or costumers.